Are mouflon Ovis gmelini musimon really grazers? A review of variation in diet composition. (21st January 2013) - Marchand, Pascal; Redjadj, Claire; Garel, Mathieu; Cugnasse, Jean‐Marc; Maillard, Daniel; Loison, Anne
Abstract: We reviewed data on the diets of mouflon (Mediterranean island populations Ovis gmelini musimon and introduced hybridized populations Ovis gmelini musimon × Ovis sp.) from 33 field studies (comprising 51 independent data points suitable for analysis) to detect general patterns in the botanical composition of the diet and identify ecological factors explaining its variation. We expected mouflon, generally classified as grazers, to include botanical entities other than grass in their diet, especially when they are forced to do so by low resource availability, and in certain seasons. Diet composition was investigated based on samples of rumen content and faeces. We combined these data with environmental characteristics at each site using a co‐inertia analysis. As expected, grass often constituted the highest proportion in the diet (in 28 of the 51 data points) and represented on average 35% (range = 0–91%) of mouflon diet, confirming the importance of this food for the species. However, referring strictly to commonly used thresholds (>75% or >90%) shows that the classification of mouflon as grazers could be questioned. Indeed, forbs and shrubs constituted 24% (range: 0–93%) and 16% (range: 0–55%) of their diet, respectively, so that mouflon should at least be considered as variable grazers. Forbs represented a high percentage of the overall diet in the Kerguelen Archipelago, southern Indian Ocean (autumn and winter: 73%) and Teide National Park, Canary Islands, Spain (autumn and winter: 83%), whereas shrubs represented a high proportion of the overall diet in Mediterranean areas (19%). Diet composition varied with spatio‐temporal variation in forage availability (documented as habitat related or seasonal variation), confirming that mouflon are able to feed on a large variety of plants. Further investigations concerning both digestive morphology and consequences of the inclusion of browse in the diet on population dynamics of mouflon are needed to understand the persistence of this species over a wide range of habitats despite a potential mismatch between its digestive ability and its observed diet.